Interconnection between Subject and Meta-Subject Results in the "Profile of Learning Outcomes" of First-Graders - Voronkova I.V.,; Ulyashev K.D., (Психолого-педагогические исследования, 2019)
The article considers the problem evaluation of meta-subject educational results in the light of the introduction of new educational standards for primary general education. One of the adequate tools for assessing meta-subject results, which are trained, is subject diagnostics. The subject of such a diagnosis can be both the level of various universal actions, and the nature of mastering the subject methods of action. The article contains examples of tasks used in the international tournament first-formers, conducted by the FSBEI HE in the "NCSPU". The peculiarities of the tasks of the proposed subject diagnostics are: a) the optimal ratio of diagnosed meta-subject and subject results; b) designing tasks in such a way that terms and sign-model means are understood in the same way in different learning systems. The analysis of the fulfillment of tasks by first-graders made it possible to construct a profile of the results of first-graders and conclude that the achievement of the objective result is a condition for achieving the meta-subject.